A Project feasibility study on the local manufacture of Clinical Weighing Scales - Gomez, Aurelio; Oliva, Honesto; Sapit, Alden; Sy, Vincent (Diliman, Quezon City College of Engineering, 1989)
As part of its national health policy, the Department of Health regularly conducts a weight monitoring program to determine the growth of pre-school children. The Nutrition Service is the agency tasked with the implementation of this program which has being conducted since 1968. As a tool for measuring the weight of children, weighing scales have been proven indispensable. This program also encountered some operational problems, particularly on the use of weighing scales. In 1985, Operation Timbang, an annual weighing of children 0-83 months old covered only 11% of the total children population and 70% of the regions in the Philippines. The Department of Health considers the following factors as the causes for these low percentages: a) lack of or absence of weighing scales b) type of weighing scales and their limitations in their own area of use. Among the limitations, ease of use, and portability and durability, since most of the children weighed can be found in outlying rural areas, are frequently mentioned. To determine the feasibility of locally manufacturing clinical weighing scales. In the light of the problems encountered regarding the operation of the weighing scale, this feasibility study is concerned more with finding a satisfactory solution to factor (a) mentioned in the Introduction. But nevertheless, it also expects to find a satisfactory answer to the second problem of correct weighing scale type. The market study conducted came out with a result that the requirements of the Department of Health for clinical weighing scales was big enough to merit further study of the technical, financial, and socio-economic aspects of putting into operation a local plant devoted solely to the manufacture of clinical weighing scale. A capacity of 30 kilograms was chosen to be the maximum load that can be weighed on this type. A total of 7,622 clinical weighing scales over ten years were seen to be the demand. This number is broken down to a demand of 2,503 in the first year of production and an average of 550 for each of the next nine years. The demand estimation was made with the following assumptions: *rate of population increase is 2.3% per year *children comprise 20% of the total population *midwife to total population ratio should be 1:5,000 *weighing scales break down at a constant rate of 2.18% of functioning scales per year. Analysis of the present supplying scheme of the Department of Health is seen to be a serious factor that causes the operational problems of the weighing scales. Foreign sources mean more expensive prices for the product and service, and longer down time for any broken down scale/ With the establishment of a local manufacturer, these problems are considerably lessened if not eliminated. Local manufacturers of weighing scales already exist but they produce only commercial types of scales. That is why one can find in the local market such types as the bathroom scale, the bar scale, hanging scale, and beam type of scale/ Minor differences distinguish these types from the clinical weighing scale, like the graduations, capacities, materials used and finishing. Under the technical study, it was found out that technology is available locally that would be able to make a clinical weighing scale of good quality. The manufacturing process of commercial types of scales is basically the same to that of clinical types. Since the group is planning for a ten year horizon, adjustments in costs were made by increasing material costs to a 10% increase every year while labor costs were increased by 5% a year. Plant capacity was derived to be about 30 scales a day. With regards to the production schedule, two alternatives were considered. Alternative 1 was to produce each year according to the demand forecast. Alternative 2 was to produce all of the 7,622 weighing scales within one year and then distribute them each according to the demand forecasted. Technically, both of these alternatives were feasible, so both were carried over to the financial study for further analysis. The Financial analysis showed that the second alternative was better in terms of returns though both showed a net profit in most of the ten years. Financial analysis was made with a sales price of P950 which is the prevailing price for commercial types. The justification for this is that should infeasibility occur at the prevailing price then the new product cannot be as competitive anymore. Financing is to be made through a commercial loan from financial institutions. With a going rate of 24.5%, the initial loan of 1.5 million pesos would be for a period of 5 years. This would be used for the start up of the plant. Another loan would be availed of on the fifth year to supplement the cash balance of the firm and keep it above P50,000 This loan would be fully repaid during the following year. Foreign exchange savings would be realized with the establishment of the plant. Local industry would also take advantage of being required to support the needs of the new plant. Local technology and labor would be completely utilized. The benefits may be also realized as indicated by the internal rate of return, the net value and the return on investment. After passing the marketing, technical, financial, and financing studies, the socio-economic analysis further supports the overall conclusion that the establishment of a local manufacturing company for clinical weighing scales is feasible.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Scales (Weighing instruments); Participatory monitoring and evaluation (Project management)